Porządek konstytucyjny a etnokratyzm elit politycznych w Karaczajo-Czerkiesji - Bodio, Tadeusz (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
One of the main causes of the anarchy in the political life of Karachay-Cherkessia is the lack of a genuine compromise between the ethnic communities concerning the questions of the political system of the republic. An attempt to develop such a compromise took place in June 1996 and ended by reaching a specific ‘constitutional pact.’ However, this compromise did not start a consolidation process among the elites on the basis of the constitution. On the contrary, it turned out to be short-lived and even expanded the field of conflicts. The republic was on the brink of civil war as early as in 1999. In the following decade, a state of permanent tensions continued. It resulted with alternating crises of power and an attempt to take over the parliament and government buildings by national minorities with the use of force. The author of this article tries to explain the causes of the political instability in Karachay-Cherkessia. He mainly focuses on the study of the constitutional fundaments of the legal and political order and its confrontation with the reality of political life in the republic. Out of this confrontation there emerges a ‘loop transformation’ syndrome, which poses a threat to the security and territorial integrity of Karachay-Cherkessia.
The constitutional order and ethnocracy among the political elite in Karachay-Cherkessia